Desain dan Implementasi Sistem Pengendalian Otomatis untuk Mengatur Debit Air Pada Prototipe Bendung sebagai Pencegahan Banjir - Gun Gun Maulana; Suharyadi Pancono; Anastasia Mia (Maranatha University Press, 2018)
Weir is a construction which is used to withstand the rate of water, and ensure water is distributed evenly. In Indonesia there are many weirs are controlled manually. It is less effective because of many human errors, for example in Garut (21/09/2016) and Bekasi (11/20/2014, 04/21/2016). In this study, the automatic weir control system was designed using VDI 2206 design method. Data of water level and flow sensor were processed by a fuzzy logic method to determine the opening of sluice and condition of the weir (safe/danger). Data is displayed on interface based on Microsoft Visual Studio. The test results on the prototype (32x20x18cm) indicate system can work automatically with 99.7% accuracy. The error is affected by ultrasonic sensor error: 5,61% and water flow sensor: 4,83%. Interface show sensor data from microcontroller can be displayed in real time. Benefits of this system are it is easy to control and monitor the weir, water flow is distributed evenly, and provides early warning information to anticipate flooding.